COMPARISON OF THE ACCURACY OF MANUAL CEPHALOMETRY RADIOGRAPHIC MEASUREMENTS AND WEB-BASED DIGITAL SOFTWARE - Yustisia Puspitasari; Sitti Fadhilah Oemar Mattalitti; Eva Novawaty; Neny Roeswahjuni (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Determining anatomical landmarks - in the cranium, maxilla and mandible - as well as measuring skeletal and dental angles on cephalometric radiographs are supporting examinations that determine important diagnoses in orthodontic treatment. Traditionally, cephalometric analysis has been performed by tracing radiographic landmarks on acetate overlays and measuring linear and angular variables using protractor. However, despite its widespread use in orthodontics, the technique is time consuming and has several drawbacks, including a high risk of error in tracing, landmark identification, and measurement. Objective: to evaluate the difference of cephalometric measurements using manual and digital technique. Method: pre-treatment cephalometric digital radiographs of 40 patients were traced manually and digitally using WebCeph Ver. 1.0.0 computer software program by the same investigator. A total of 8 anatomical landmarks were located and five angular measurements based on Steiner Analysis were measured. Independent t-tests and Mann-Whitney tests were used to compare the difference of manual and digital measurements. Result: the p-values for SNA, SNB, ANB, I-NA, I-NB were greater than 0.05 (p>0.05). Conclusion: There were no significant difference between manual and digital tracing cephalometric technique using WebCeph for SNA, SNB, ANB, I-NA and I-NB Keywords: Cephalometric measurement, Digital cephalometric analysis, Steiner Analysis, Tracing cephalometry, WebCeph